Revascularization and tissue regeneration of an empty root canal space is enhanced by a direct blood supply and stem cells - Srisuwan T. (2014)
Background: Regenerative endodontics is an innovative treatment concept aiming to regenerate pulp, dentin and root structures. In the diseased or necrotic tooth, the limitation in vascular supply renders successful tissue regeneration/generation in a whole tooth challenging. The aim of this study is to evaluate the ability of vascularized tissue to develop within a pulpless tooth using tissue engineering techniques. Materials and methods: A pulpless tooth chamber, filled with collagen I gel containing isolated rat dental pulp cells (DPC) and angiogenic growth factors, was placed into a hole created in the femoral cortex or into its own tooth socket, respectively. The gross, histological and biochemical characteristics of the de novo tissue were evaluated at 4 and 8weeks post-transplantation. Results: Tooth revascularization and tissue generation was observed only in the femur group, confirming the important role of vascular supply in tissue regeneration. The addition of cells and growth factors significantly promoted connective tissue production in the tooth chamber. Conclusion: Successful revascularization and tissue regeneration in this model demonstrate the importance of a direct vascular supply and the advantages of a stem cell approach. © 2012 John Wiley & Sons A/S.